Insights Into the Genetics of the Zhonghua 11 Resistance to Meloidogyne graminicola and Its Molecular Determinism in Rice - Nguyen, Hue Thi; Mantelin, Sophie; Ha, Cuong Viet; Lorieux, Mathias; Jones, John T.; Mai, Chung Duc; Bellafiore, Stéphane (Frontiers in Plant Science, 2022)
Meloidogyne graminicola is a widely spread nematode pest of rice that reduces crop yield up to 20% on average in Asia, with devastating consequences for local and global rice production. Due to the ban on many chemical nematicides and the recent changes in water management practices in rice agriculture, an even greater impact of M. graminicola can be expected in the future, stressing the demand for the development of new sustainable nematode management solutions. Recently, a source of resistance to M. graminicola was identified in the Oryza sativa japonica rice variety Zhonghua 11 (Zh11). In the present study, we examine the genetics of the Zh11 resistance to M. graminicola and provide new insights into its cellular and molecular mechanisms. The segregation of the resistance in F2 hybrid populations indicated that two dominant genes may be contributing to the resistance. The incompatible interaction of M. graminicola in Zh11 was distinguished by a lack of swelling of the root tips normally observed in compatible interactions. At the cellular level, the incompatible interaction was characterised by a rapid accumulation of reactive oxygen species in the vicinity of the nematodes, accompanied by extensive necrosis of neighbouring cells. The expression profiles of several genes involved in plant immunity were analysed at the early stages of infection during compatible (susceptible plant) and incompatible (resistant plant) interactions. Notably, the expression of OsAtg4 and OsAtg7, significantly increased in roots of resistant plants in parallel with the cell death response, suggesting that autophagy is activated and may contribute to the resistance-mediated hypersensitive response. Similarly, transcriptional regulation of genes involved in hormonal pathways in Zh11 indicated that salicylate signalling may be important in the resistance response towards M. graminicola. Finally, the nature of the resistance to M. graminicola and the potential exploitation of the Zh11 resistance for breeding are discussed.